The effect of depression level on attention performance in smokers - Taşpınar, Aysu; Pakyürek, Gün (Journal of Dependence, 2020)
Objective: The aim of this study is to determine how differentiated smokers and non-smokers’ attention performance according to their depression levels.Method: The sample of the study consisted of 62 participants between 19-26 years of age who have been continuing their undergraduate education at Aydın Adnan Menderes University. Data collection tools were Fagerström Nicotine Dependence Test, Beck Depression Inventory, Nicotine Stroop and Trail Making Test. Participants have been divided into 4 groups according to Beck Depression Inventory cut off points as minimal, mild, moderate and severe depression. Then, Nicotine Stroop has been used for selective attention performance and the Trail Making Test has been applied to measure the complex attention of the participants.Results: Results showed that cigarette dependence levels and depression levels differ significantly. There werenot significant differences in attention performance as participants' depression and smoking dependence levels.Conclusion: The findings suggested that new studiesare needed to better understand the effect of depression level on attention performance in smokers by determining the level of smoking with physiological measurements, changing the severity of abstinence level and other pathological disorders variables.
Keywords: Smoking; depression; dependence; nicotine; attention